PRODAMAS chatbot: Aflask and support vector machine based implementation - Mustain, Riefyal Arshyza; Muhajir, Muhammad; Ferdias, Pandri; Saputra, Nurirwan (Universitas Islam Negeri Raden Intan Lampung, 2023)
In accelerated and equitable development in the Kediri City, the Kediri City Government launched the Community Empowerment Program called Prodamas. Prodamas aims to develop and encourage community participation in development at the Neighbourhood Level. To increase the dissemination of information about Prodamas, digital technology can be used as an information service provider. One of them is Chatbot. To develop Chatbots, Natural Language Processing, which is a branch of Artificial Intelligence, has become the most frequently used computer program. This Prodamas chatbot development uses the pattern matching method as an answer search algorithm and Support Vector Machine (SVM) classification as a method to see the machine's level of accuracy in answering questions given by users. Furthermore, the chatbot will be connected to WhatsApp so that it is expected to be able to provide and provide information about Prodamas. The results of testing the chatbot response with new questions provide an accuracy of 79%. Then testing the classification of the new question text with SVM. Obtained an accuracy of 88% with a precision value of 91% and a recall of 88%.